Território, política e infraestruturas: a influência do Governo Federal na política urbana dos municípios brasileiros / Territory, politics and infrastructures: the influence of the federal government in urban policy of the Brazilian municipalities - Fabricio Gallo (Sociedade & Natureza)
The evolution of Brazilian federalism (result of the influence and power of oligarchic elites, the different constitutional texts made and policies designed to collect taxes) shows one of the forms of how the Brazilian government uses the territory to effect the exercise of power. In the country, this use takes place by the imposition of rules that regulate and create tension among the entities, and mechanisms of distribution and redistribution of resources among federal agencies acquire great importance because they allow a bigger or lesser autonomy in public administration. The text aims to analyze the voluntary transfers of resources from the Federal Government to the municipalities. These Covenants act as a mechanism that can be configured in promoter of new selectivity and hierarchies between places. With the aim to understand the materialization of public resources in the territory, our analysis intends to identify how the Brazilian government makes use of constitutional mechanisms to enlarge and improve the urban infrastructure in the municipal scale.